RECOMMENDATIONS CONCERNING THE APPLICATION OF SMOKE AND THERMAL TRANSMISSION: Array - Prisyajnyuk, V.; Semychayevsky, S.; Yakimenko, M.; Osadchuk, M.; Kurtov, O.; Milutin, O. (Municipal economy of cities. Series: «Economy science», 2019)
At the Ukrainian Research Institute of Civil Protection, within the framework of the research work "Smoke and heat removal means", recommendations were made on the basis of analytical and experimental researches on the use of portable means of smoke and heat removal, which determine the order of use protection of portable smoke and heat removal devices designed to control convective fire flows by blowing air and removing tion of combustion products. The structure of recommendations on the use of portable means of smoke and heat removal is given. The methods of creating the necessary conditions for extinguishing a fire using portable means of smoke and heat removal are described, namely: suction and further removal of smoke outside, injection of fresh air into the smoky room and simultaneous removal of smoky and polluted air and injection of fresh air with the supply of fresh air. and heat removal.General information is presented, which shows the purpose and procedure of the forced convection of smoky premises using portable means of smoke and heat removal, the general algorithm of actions of personnel of fire and rescue units during the use of such facilities, as well as standard schemes for their location. In addition, recommendations are given for the injection of air by means of portable means of smoke and heat removal in rooms where there was a fire and the basic approaches to choosing the distance from the portable means of smoke and heat removal to the inlet door opening, as well as the approximate relations between the inlet and exhaust openings are described. The issue of personnel safety during the use of such means is additionally disclosed, as well as the main technical characteristics of individual means of injection type of action are given. Thus, after agreement with the Emergency Response Department, the developed recommendations will be used in the practical activities of the fire and rescue units. The implementation of the recommendations will help to improve the efficiency of firefighting rescue units in conditions of high temperature and heavy smoke.